Room quality and composition matters: Children's verbal and numeracy abilities in Australian early childhood settings. (April 2018) - Niklas, Frank; Tayler, Collette
Abstract: Early literacy and numeracy competencies are an important foundation for successful school achievement. In this large-scale study data from over 2000 Australian children who attended formal early childhood education and care (ECEC) settings were analysed to identify predictors of these competencies. In addition to child and family characteristics, the quality and the composition of the attended ECEC rooms were included in hierarchic linear models. A significant amount of variance of both, verbal and numeracy competencies, was explained by child and family characteristics. In addition, room composition reflected by mean intelligence of the children in the rooms in which children participate and program quality were significant predictors. Children with lower in comparison to higher intelligence scores were affected more by being present in lower rather than higher average intelligence in the attended rooms. These and other findings are discussed in regard to the implications for children attending ECEC settings in Australia. Highlights: Our sample consisted of more than 2000 Australian children aged 4 years old. Child and family characteristics and ECEC room quality and composition were analysed. Better program quality was associated with greater children's cognitive outcomes. The same was true for a greater mean intelligence of children attending the same room. Interactions between room-level and child-level variables are analysed and discussed.